2021
DOI: 10.1186/s12906-020-03175-0
|View full text |Cite
|
Sign up to set email alerts
|

Germacrone alleviates neurological deficits following traumatic brain injury by modulating neuroinflammation and oxidative stress

Abstract: Background Germacrone (GM) is a terpenoid compound which is reported to have anti-inflammatory and anti-oxidative effects. However, its role in treating traumatic brain injury (TBI) remains largely unknown. Methods Male C57BL/6 mice were divided into the following groups: control group, TBI group [controlled cortical impact (CCI) model], CCI + 5 mg/kg GM group, CCI + 10 mg/kg GM group and CCI + 20 mg/kg GM group. GM was administered via intraperito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Our results indicated that GE treatment prevented the LPS-induced cognitive impairments by perturbing neuroin ammation. Consistent with previous studies, GE alleviates neurological de cits in traumatic brain injury via repressing neuroin ammation and oxidative stress 25 . Multiple studies revealed that neuroin ammation is related to the neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results indicated that GE treatment prevented the LPS-induced cognitive impairments by perturbing neuroin ammation. Consistent with previous studies, GE alleviates neurological de cits in traumatic brain injury via repressing neuroin ammation and oxidative stress 25 . Multiple studies revealed that neuroin ammation is related to the neurodegenerative diseases.…”
Section: Discussionsupporting
confidence: 91%
“…The Curcuma species have been used in traditional Chinese medicine for more than one thousand years 18 . The curcuminoids and volatile oil extracted from Curcuma species have been extensively studied due to their biological activities and pharmacological effects, including anti-in ammatory, antitumor, antioxidant, antimicrobial properties, and therapeutical promise on the nervous, digestive, and cardiovascular systems [19][20][21][22][23][24][25] . Germacrone (GE) has been identi ed as one of the main ingredients in Curcumae Wenyujin Y.H.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, this chronic pain condition is well established by using CCI to sciatic nerve and STZ animal model of peripheral nerve injury. 45,46 Again, these models are associated with development of characteristic symptoms of neuropathy like allodynia and hyperalgesia. The present study showed that CCI and STZ lead to elevated levels of proinflammatory cytokines like TNF-α, IL-1ꞵ, and IL-6 and total calcium in homogenate of sciatic nerve.…”
Section: Groupsmentioning
confidence: 99%
“…The permeability of the blood-brain-barrier (BBB) increases the infiltration of circulating monocytes, lymphocytes, and neutrophils inside the brain parenchyma within 24 hours of TBI. Because of this, the complement system is stimulated and the inflammatory cytokines like tissue necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β) that are proinflammatory cytokines are released [43][44][45][46]. When these inflammatory cytokines are released, BBB dysfunction and brain edema occur.…”
Section: Traumatic Brain Injury and Neuroinflammationmentioning
confidence: 99%